Our kids : the American Dream in crisis - Putnam, Robert D. (Simon & Schuster, 2015)
"What has happened to the Land of Opportunity? The promise of the American Dream is that anyone, regardless of his or her origins, can have a fair start in life. If we work hard, we can get a good education and achieve success. But over the last several decades a disturbing 'opportunity gap' has unexpectedly emerged between kids from 'have' and 'have-not' backgrounds. The central tenet of the American Dream--that all children, regardless of their family and social background, should have a decent chance to improve their lot in life--is no longer 'self-evident.' Robert Putnam begins this groundbreaking examination of our national prospects with the story of his high school class of 1959 in Port Clinton, Ohio. The vast majority of those students--'our kids' to everyone in town--went on to lives better than those of their parents. They raised their children with the same expectations. But those children--and their children--have not fared so well in an age of fragile families, crumbling communities, and disappearing jobs. Their lives reflect the diminishing opportunities that haunt so many American kids today. Putnam tells poignant stories of rich and poor kids from cities and suburbs across the country, drawing on a formidable body of research undertaken especially for this book. Our Kids is a rare combination of moving personal narratives and authoritative evidence--and for that reason, all the more troubling to read. It is a signal contribution to the ongoing discussion about inequality in America, a deeply informed and perceptive analysis of our country at a critical time. In the final chapter, Putnam offers suggestions for how we might halt this decline in opportunity and restore a greater chance for upward mobility."--Book jacket.